(untitled) (World Bulletin of Social Sciences, 2023)
This article is written about using interactive methods in teaching simultaneous translation. Psycholinguistics studies the processes of speech production and perception in relation to the language system. This science seeks to interpret language as a dynamic system of human speech activity. Since the object of psycholinguistics is speech activity, and the object of translation theory is a special type of speech activity, the tasks of these disciplines are largely compatible with each other.